Mathematical Abilities in Children With Developmental Language Disorder. - Cross, Alexandra M.; Joanisse, Marc F.; Archibald, Lisa M. D. (Language, Speech & Hearing Services in Schools, 2019)
Purpose: This review article provides a scoping review of the literature on mathematical abilities in developmental language disorder (DLD). Children with DLD typically struggle with learning in school; however, the mechanism by which DLD impacts academic success is unclear. Mathematics involves demands in the multiple domains and therefore holds potential for examining the relationship between language and academic performance on tasks mediated by verbal and nonverbal demands. Method: A scoping review was performed via computerized database searching to examine literature on mathematics and DLD. The 21 review articles meeting inclusion criteria compared children with typical development or DLD on various tasks measuring numerical cognition. Results: Children with DLD consistently performed below peers with typical development on number transcoding, counting, arithmetic, and story problem tasks. However, performance was similar to peers with typical development on most number line, magnitude comparison, and conceptual mathematics tasks. Conclusions: The findings suggest a relationship between DLD and mathematics was characterized by more detrimental performance on tasks with higher verbal demands. Results are discussed with respect to typical academic curricula and demonstrate a need for early identification and intervention in DLD to optimize academic outcomes.